2023
DOI: 10.1051/sicotj/2023001
|View full text |Cite
|
Sign up to set email alerts
|

No clinical difference at mid-term follow-up between TiN-coated versus uncoated cemented mobile-bearing total knee arthroplasty: a matched cohort study

Abstract: Introduction: Nitride-based ceramic coating was introduced into surgical implants to improve hardness, reduce abrasion, and decrease the risk of metal-induced adverse reactions, especially for patients with suspected or identified metal hypersensitivity. The study aimed to evaluate the effectiveness and safety of a titanium nitride (TiN) coated prosthesis with a mobile bearing design. Methods: This was a retrospective matched-cohort study from a single center, comparing clinical outcomes between patients recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 35 publications
1
0
0
Order By: Relevance
“…The data support that the ACS III system provided excellent long-term outcomes and is well suited for the treatment of end-stage osteoarthritis of the knee joint when compared to other cemented systems. This is in line with a recent systematic review that reported that TiN-coated prostheses are not inferior to uncoated TKAs [ 18 ] and a mid-term follow-up matched-cohort study that reported satisfactory clinical outcomes and low revision rates for TiN-coated TKA [ 19 ]. Van Es et al showed no difference in mid-term survival and function among cemented, uncemented, and hybrid fixation in mobile-bearing ACS TKA [ 20 ].…”
Section: Discussionsupporting
confidence: 89%
“…The data support that the ACS III system provided excellent long-term outcomes and is well suited for the treatment of end-stage osteoarthritis of the knee joint when compared to other cemented systems. This is in line with a recent systematic review that reported that TiN-coated prostheses are not inferior to uncoated TKAs [ 18 ] and a mid-term follow-up matched-cohort study that reported satisfactory clinical outcomes and low revision rates for TiN-coated TKA [ 19 ]. Van Es et al showed no difference in mid-term survival and function among cemented, uncemented, and hybrid fixation in mobile-bearing ACS TKA [ 20 ].…”
Section: Discussionsupporting
confidence: 89%